2014
DOI: 10.3390/ijerph110302698
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Agricultural Land Use Change in the Middle Reach of the Heihe River Basin, Northwest China

Abstract: The Heihe River Basin (HRB) is the second largest inland river basin in arid Northwest China. The expanding agricultural irrigation, growing industrialization, and increasing urban development in the middle reach have depleted much of the river flow to the lower reach, degrading the corresponding ecosystems. Since the enactment of the State Council of China’s new HRB water allocation policy in 2000 tremendous land use and land cover (LULC) changes have taken place to reduce water consumption in the middle reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…They found that farmland and water areas in middle reaches of HRB increased by 25.53% and 109.21% during 1985-1997, respectively. Although the changes in water areas of Fu et al (2014) is different from our researches, the water areas changes (increased by 109.21% during 1985-1997) assessed by Lu et al (2003) is similar to our research (increased by 162.02% during 1986-2000). In addition, the farmland expansion rate (25.53%) of Lu et al (2003) is also very similar to our research (24.41%).…”
Section: Comparisons Of Research Results Of This Paper With Other Ressupporting
confidence: 64%
See 3 more Smart Citations
“…They found that farmland and water areas in middle reaches of HRB increased by 25.53% and 109.21% during 1985-1997, respectively. Although the changes in water areas of Fu et al (2014) is different from our researches, the water areas changes (increased by 109.21% during 1985-1997) assessed by Lu et al (2003) is similar to our research (increased by 162.02% during 1986-2000). In addition, the farmland expansion rate (25.53%) of Lu et al (2003) is also very similar to our research (24.41%).…”
Section: Comparisons Of Research Results Of This Paper With Other Ressupporting
confidence: 64%
“…However, the change trend of water areas is a little different. Water areas in middle reaches of HRB showed negative change trend in our research while that of Fu et al (2014) present a negative change trend. In spite of the difference in research period, the unmatched land use classification of water areas could also attribute to the difference.…”
Section: Comparisons Of Research Results Of This Paper With Other Resmentioning
confidence: 64%
See 2 more Smart Citations
“…The HRB is a typical inland river ecosystem, which includes natural vegetation, irrigated crop, desert and terminal lakes. The middle course of the basin has an agricultural history over more than 2000 years, while the lower reaches are located at the alluvial fan -supporting local human civilization and ecosystem development (Fu et al, 2014). Increasing agricultural development and changing climate and hydrology over the past 2000 years have significantly changed use of land and water resources and have modified the catchment vegetation system (Lu et al, 2015a;Zhao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%